2018
DOI: 10.1158/1078-0432.ccr-18-0279
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-cadherin Enhances IGF1–IGF1R Pathway Activation and Sensitizes Breast Cancers to Anti-IGF1R/InsR Inhibitors

Abstract: Insulin-like growth factor 1 (IGF1) signaling regulates breast cancer initiation and progression and associated cancer phenotypes. We previously identified E-cadherin () as a repressor of IGF1 signaling and in this study examined how loss of E-cadherin affects IGF1R signaling and response to anti-IGF1R/insulin receptor (InsR) therapies in breast cancer. Breast cancer cell lines were used to assess how altered E-cadherin levels regulate IGF1R signaling and response to two anti-IGF1R/InsR therapies. proximity li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 64 publications
(61 reference statements)
10
69
1
Order By: Relevance
“…This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38]. Furthermore, in breast cancer models, loss of E-cadherin and the subsequent activation of IGF1R signaling results in increased sensitivity to dual IGF1R/Insulin receptor inhibitors, and Akt inhibitors that target downstream receptor pathway activation, even in the presence of activating PIK3CA mutations [36,37]. Interestingly, increased expression of IGF1 is seen in ILC compared to IDC [27,36,39], consistent with reported pathway activation [36,37].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38]. Furthermore, in breast cancer models, loss of E-cadherin and the subsequent activation of IGF1R signaling results in increased sensitivity to dual IGF1R/Insulin receptor inhibitors, and Akt inhibitors that target downstream receptor pathway activation, even in the presence of activating PIK3CA mutations [36,37]. Interestingly, increased expression of IGF1 is seen in ILC compared to IDC [27,36,39], consistent with reported pathway activation [36,37].…”
Section: Discussionsupporting
confidence: 94%
“…Previously we have shown that loss of E-cadherin promotes hypersensitization of PI3K/Akt pathway activation in response to IGF1, independent of PAPP-A [36], as well as oncogenic mutations in the PI3K/Akt pathway that are prevalent in ILC [5]. This is consistent with other reports demonstrating that E-cadherin-mediated adhesion negatively regulates IGF1R activation [37,38]. Furthermore, in breast cancer models, loss of E-cadherin and the subsequent activation of IGF1R signaling results in increased sensitivity to dual IGF1R/Insulin receptor inhibitors, and Akt inhibitors that target downstream receptor pathway activation, even in the presence of activating PIK3CA mutations [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…ILC is the 6 th most common cancer in women, with an estimated 40,000 new cases in 2019, despite accounting for a smaller proportion of breast cancer cases (~15%) compared to IDC (~75%) 1 . ILC shows distinct signaling in pathways essential for breast cancer growth and proliferation compared to IDCsuch as the WNT4 signaling in response to estrogen stimulus or blockade 2,3 , increased PI3K/Akt signaling 4,5 , enhanced IGF1-IGF1R activation 6 , and dependency on ROS1 7 , which suggest that ILC could benefit from unique treatment strategies. The most distinguishing molecular feature of ILC is loss of E-cadherin, largely arising from inactivating CDH1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has shown that E‐cadherin improves IGF1R recruitment to adherens junctions, possibly resulting in receptor sequestration and signaling repression. The loss of functional E‐cadherin would impair the adherens junction formation, and release IGF1R to re‐localize to the entirety of the cell membrane where the IGF1 ligand is easily bound for initiating cancer signaling …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GRIK3 is enriched in the neuroactive ligand receptor interaction pathway and haploinsufficiency of GRIK3 may be responsible for the severe developmental delay. 2,9,10 Interestingly, a previous study indicated that, in breast cancer, multiple estradiol (E2) stimulated or inhibited genes also enriched in the neuroactive ligand receptor interaction pathway were able to affect the cell proliferation. 11 On the basis of the current studies, we proposed that GRIK3 might function in the development of breast cancer.…”
Section: Introductionmentioning
confidence: 99%